PENGEMBANGAN KOMPETENSI SUMBER DAYA APARATUR UNTUK MENINGKATKAN KINERJA PADA KANTOR KECAMATAN SUNGAI KUNJANG KOTA SAMARINDA - Agus Yuliantoro (Jurnal Administrative Reform, 2017)
This study was to describe the Competence Development Resources Administrative Region in the Framework of Improving Performance in the River District Office Kunjang Samarinda, to analyze how resource development of personnel competence areas in order to improve performance at the District Office River City Samarinda Kunjang , to determine the factors that support and inhibit the Competence Development Resources Administrative Region in the Framework of Improving Performance in the River District Office Kunjang Samarinda. With the focus of research is regarding the performance of service following; responsiveness, responsibility and accountability; factors that support and hinder the performance of service as follows: organizational structure, human resources. From the results of the study there was a supportive factor in the River District Office Service Performance Kunjang Samarinda includes the delegation of authority within the organization, the utilization rate of the apparatus according to specialties, the execution of the task will be able to provide good service to the community, while the limiting factor is resources development fund officials were late down for competence development personnel resources, is limited personnel in following Opportunity Training and this imbalance needs Required Skills By Position.